Fresno State vs. San Jose State Evening Football Game at Bulldog Stadium - Watkins, Howard::::::::: (1989)
Scoreboard info: 4th quarter with 6:11 minutes left; attendance 35, 353; Fresno state 31 and San Jose State 24